Rapid, Point-of-Care Microwave Lysis and Electrochemical Detection of Clostridioides difficile Directly from Stool Samples - Lovleen Tina Joshi; Emmanuel Brousseau; Trefor Morris; Jonathan Lees; Adrian Porch; Les Baillie (Bioengineering, 2024)
The rapid detection of the spore form of Clostridioides difficile has remained a challenge for clinicians. To address this, we have developed a novel, precise, microwave-enhanced approach for near-spontaneous release of DNA from C. difficile spores via a bespoke microwave lysis platform. C. difficile spores were microwave-irradiated for 5 s in a pulsed microwave electric field at 2.45 GHz to lyse the spore and bacteria in each sample, which was then added to a screen-printed electrode and electrochemical DNA biosensor assay system to identify presence of the pathogen’s two toxin genes. The microwave lysis method released both single-stranded and double-stranded genome DNA from the bacterium at quantifiable concentrations between 0.02 μg/mL to 250 μg/mL allowing for subsequent downstream detection in the biosensor. The electrochemical bench-top system comprises of oligonucleotide probes specific to conserved regions within tcdA and tcdB toxin genes of C. difficile and was able to detect 800 spores of C. difficile within 300 µL of unprocessed human stool samples in under 10 min. These results demonstrate the feasibility of using a solid-state power generated, pulsed microwave electric field to lyse and release DNA from human stool infected with C. difficile spores. This rapid microwave lysis method enhanced the rapidity of subsequent electrochemical detection in the development of a rapid point-of-care biosensor platform for C. difficile.